PENGARUH LAMA PENYIMPANAN TERHADAP VIABILITAS BENIH KEDELAI (Glycine max (L) Merrill) VARIETAS ANJASMORO - Nur Hayati; Setiono Setiono (Universitas Muara Bungo, 2021)
The purpose of this study was to determine the effect of storage time and best storage time on the viability of Anjasmoro soybean seeds. This research was conducted in Benteng Village, Sungai Manau District, Merangin Regency with an altitude of ± 204 m asl and a temperature ranging from + 25-31oC. This research was conducted on 17 October 2019 to 17 February 2020.This study used a completely randomized design (CRD) with 5 treatments, namely: P0 (without storage), P1 (1 month of storage), P2 (2 months of storage), P3 (3 months of storage) and P4 (4 months of storage). The parameters observed were the percentage of normal sprouts (%), percentage of dead seeds (%), percentage of damaged germination (%), germination rate (days), hypocotyl length (cm) and root length (cm). To see the effect of treatment on the observed variables, the data obtained were analyzed statistically using variance fingerprints and if the results of the analysis had a significant effect, then proceed with the Duncan New Multiple Range Test (DNMRT) at the 5% real levelThe results showed that storage time affected the percentage of normal sprouts (%), percentage of dead seeds (%), percentage of damaged germination (%), germination rate (days), hypocotyl length (cm) and root length (cm) of Anjasmoro soybean seeds. . Storage time of 1 month (P1) is the best treatment for the viability of Anjasmoro soybean seeds